2018
DOI: 10.1007/s00348-018-2568-2
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of non-Newtonian droplet collisions: the role of extensional viscosity

Abstract: We investigate the collision behaviour of a shear thinning non-Newtonian fluid xanthan, by binary droplet collision experiments. Droplet collisions of non-Newtonian fluids are more complex than their Newtonian counterpart as the viscosity no longer remains constant during the collision process. Despite the complex collision dynamics, we are able to present a complete regime map based on non-dimensional Weber (We) number and impact parameter (B). We compare the collision outcomes of xanthan, glycerol and a milk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(38 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…In contrast to the drop-drop collisions [13][14][15][16][17][18], here we distinguished two regimes. In the first regime, the first drop spreads and all the successively impinging drops merge into a liquid layer on the surface.…”
Section: Of 19mentioning
confidence: 82%
See 2 more Smart Citations
“…In contrast to the drop-drop collisions [13][14][15][16][17][18], here we distinguished two regimes. In the first regime, the first drop spreads and all the successively impinging drops merge into a liquid layer on the surface.…”
Section: Of 19mentioning
confidence: 82%
“…The second regime involves a fine aerosol generated by the drop impact on the wall. When drops collide with each other, four regimes are identified [13][14][15][16][17][18], namely, coalescence, rebound, separation, and breakup. Rebound means that drops approach each other and then move apart without immediate contact because the kinetic energy is not enough for drops to pass across the gas-vapor layer between them.…”
Section: Of 19mentioning
confidence: 99%
See 1 more Smart Citation
“…The research of Pan et al [17] identified the key mechanisms governing the impact dynamics of surfactant-coated droplets in the air and imply the potential of using a small amount of surfactant to manipulate impact outcomes. Compared to the Newtonian liquids, relatively few studies [24][25][26][27][28][29][30] have been conducted for the non-Newtonian liquids, which are of relevance to, for example, polymers. For the non-Newtonian liquid, the effects of the viscosity on the deformation process and the boundary model of the droplets are investigated.…”
mentioning
confidence: 99%
“…They found that, in the collision process, the kinetic energy was dissipated due to viscous flow, and thus the critical Weber number for the reflexive separation increased with the Ohnesorge number. By combining the experimental results [24], Finotello et al [25] further experimentally investigated the collision behaviors of binary shear-thinning droplets and presented a complete regime map for collision boundaries based on the Weber number (We) and impact parameter (B).In the experiments, for the formation of high-quality and stable droplets, the transient visualization of the collision droplets is difficult to realize, so numerical simulation work is needed to compensate for this technical deficiency. Amani et al[19] simulated head-on and off-center binary droplet collisions in all the regimes [18] using a conservative level-set method.…”
mentioning
confidence: 99%